From the physical to the spiritual : understanding perceval’s journey - Tan, Li Ling (2014)
This paper explores the problem of family and the tension it creates in Chretien's Le Conte du Graal. The protagonist, Perceval, is caught between his physical family and his spiritual family and this paper analyses the root of this tension as well as how Chretien attempts to resolve this issue in the text.